PENGARUH CITRA MEREK DAN KESADARAN MEREK TERHADAP EKUITAS MEREK SIRUP CAIR DALAM KEMASAN SIRUP KARTIKA (Studi pada Pelanggan Sirup Kartika di Kecamatan Gubug Purwodadi) - Dany Tri Saputro, 14.05.51.0139; Sutejo, Bambang (Students' Journal of Economic and Management, 2018)
This study aims to analyze the influence of brand image and brand awareness of the liquid syrup brand equity in Kartika Syrup packaging. The population in this study is the villagers Gubug who had consumed / bought the product of syrup in the packaging of bottles brand "Sirup Kartika". Minimum sample size in this study, as many as 100 people. Sampling technique using purposive sampling. The sample criteria in this study were villagers Gubug who consume syrup of respondents aged at least 17 years old. The analytical tool used is the test of validity, reliability, multiple linear regression and mediation test. The results of the analysis can be concluded that: Brand image has a positive effect on brand equity. The better the brand image, it will increase brand equity. Brand awareness positively affects brand equity. The better the brand awareness, it will increase brand equity Keywords: brand image, brand awareness and brand equity